Endoscopic Ultrasound-Guided Fine Needle Biopsy with Stylet and Suction Versus No Stylet No Suction for the Diagnosis of Pancreatic and Non-Pancreatic Lesions - Ahmed MA; Ahmed MY; Shaaban HE; Abou Elenin SEA; El-Habashi AA; Belabbes F; Tag-Adeen M; Abdellatef A; Okasha HH (International Journal of General Medicine)
Marwa A Ahmed,1 Mohamed Yousri Ahmed,1 Hossam Eldin Shaaban,2 Sameh EA Abou Elenin,3 Ahmed Ali El-Habashi,1 Fatima Belabbes,4 Mohammed Tag-Adeen,5 Abeer Abdellatef,6 Hussein Hassan Okasha6 1National Cancer Institute (NCI), Cairo University, Cairo, Egypt; 2Department of Internal Medicine and Gastroenterology, National Hepatology and Tropical Medicine Research Institute, Cairo, 11796, Egypt; 3Gastroenterology Military Medical Academy, Cairo, 11796, Egypt; 4Department of Gastroenterology and Hepatology, Cheikh Khalifa International University Hospital, Mohammed VI University of Health and Sciences, Casablanca, and Research Entity, Mohammed VI Center for Research & Innovation, Rabat, Morocco; 5Division of Gastroenterology and Hepatology, Department of Internal Medicine, Qena Faculty of Medicine, South Valley University, Qena, Egypt; 6Department of Internal Medicine, Hepatogastroenterology division, Kasr Al-Aini Hospitals, Faculty of Medicine, Cairo University, Cairo, EgyptCorrespondence: Hossam Eldin Shaaban, Email hsshaaban@aol.comBackground: Endoscopic ultrasound (EUS)-guided tissue acquisition is the procedure of choice to obtain samples to diagnose pancreatic and non-pancreatic lesions. Previous randomized trials demonstrated that using stylets during the EUS-fine needle biopsy (FNB) technique does not improve the diagnostic yield. However, little data exists regarding the role of stylet and suction in the core biopsy needle during EUS-guided tissue acquisition.Aim of the Study: This study aims to assess the efficacy and diagnostic yield of samples collected by EUS-FNB with stylet and suction versus no stylet, no suction techniques.Patients and Methods: This prospective study included 167 patients referred to the Gastroenterology Division, Internal Medicine Department, Kasr Al-Aini Hospitals for EUS-guided biopsy from pancreatic or non-pancreatic lesions from May 2021 to January 2024. Each lesion was sampled twice using an EUS-FNB 22-gauge Franseen-tip needle (Acquire; Boston Scientific, USA); one sample was collected with stylet and suction, while the other with no stylet no suction technique. Subsequently, slides were evaluated for cellularity, tissue integrity, degree of blood contamination, and diagnostic ability.Results: A total of 167 patients fulfilled the inclusion criteria, 78 females and 89 males, with a mean age of 61 years. Most lesions were pancreatic (83.2%, n = 139), while the remaining (16.8%, n = 28) were non-pancreatic. No significant differences were observed between stylet and suction versus no stylet, no suction techniques. The diagnostic performance, including sensitivity, specificity, and overall accuracy, was identical (100%) for both methods when evaluating alcohol-fixed smears in conjunction with formalin-preserved tissues collected through FNB.Conclusion: EUS-FNB tissue acquisition with and without stylet and suction provides comparable diagnostic yield and tissue quality for pancreatic and non-pancreatic lesions. The decision to use a stylet and suction should be individualized based on the clinical context and operator experience.Keywords: EUS-FNB, pancreatic lesions, non-pancreatic lesions, stylet, suction, diagnostic yield